2018
DOI: 10.1016/j.jid.2017.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Skin Commensal Malassezia globosa Secreted Protease Attenuates Staphylococcus aureus Biofilm Formation

Abstract: Skin provides the first defense against pathogenic micro-organisms and is also colonized by a diverse microbiota. Phylogenetic analysis of whole skin microbiome at different skin sites in health and disease has generated important insights on possible microbial involvement in modulating skin health. However, functional roles of the skin microbial community remain unclear. The most common sebaceous skin commensal yeasts are the basidiomycetes, Malassezia. Here, we characterized the dominant secreted Malassezia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
2
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 45 publications
(52 reference statements)
1
93
2
3
Order By: Relevance
“…is unusual in thickness (90–150 nm), morphology (inner spiralling/corrugation) and composition (predominance of (1 → 6)‐ß‐ D ‐glucan, trace of mannan with unusual polysaccharide assembly, chitin prominent in bud‐scar, lipid‐rich wall and capsule) (Figure ). Interaction with other commensal microbes might also influence pathogenicity and expression of virulence factors . Thus, these commensal yeasts are likely highly regulated by continuous interactions with the host immune system (Section 6) and these interactions ultimately determine whether the outcome is inflammation (i.e.…”
Section: Pathogenesis: Virulence Attributes Amongst Malassezia Yeastsmentioning
confidence: 99%
See 1 more Smart Citation
“…is unusual in thickness (90–150 nm), morphology (inner spiralling/corrugation) and composition (predominance of (1 → 6)‐ß‐ D ‐glucan, trace of mannan with unusual polysaccharide assembly, chitin prominent in bud‐scar, lipid‐rich wall and capsule) (Figure ). Interaction with other commensal microbes might also influence pathogenicity and expression of virulence factors . Thus, these commensal yeasts are likely highly regulated by continuous interactions with the host immune system (Section 6) and these interactions ultimately determine whether the outcome is inflammation (i.e.…”
Section: Pathogenesis: Virulence Attributes Amongst Malassezia Yeastsmentioning
confidence: 99%
“…Laboratory data indicated that phospholipase production might act in synergism with biofilm formation (layers of adhering yeasts embedded in variable quantities of extracellular matrix) to induce or exacerbate skin lesions in dogs . By contrast, a secreted aspartyl protease from M. globosa inhibited S. aureus biofilm proliferation and rapidly hydrolysed protein A, a major staphylococcal virulence factor . A correlation between biofilm formation and other virulence factors (hydrophobicity, adherence) was observed amongst 60% of 16 clinical isolates of M. furfur .…”
Section: Pathogenesis: Virulence Attributes Amongst Malassezia Yeastsmentioning
confidence: 99%
“…It is generally believed that Malassezia actively promotes disease symptoms in predisposed atopic individuals, albeit firm evidence for this causal link is missing and the mechanistic basis has not been established. Alternatively, Malassezia may also exert a protective role in AD (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This dual role of C. acnes is a feature that also extends to other skin microbes, for example Malassezia globosa . While generally accepted as the cause of seborrhoeic dermatitis, M. globosa has also been shown to secrete a potentially beneficial protease, which may prevent S. aureus biofilm formation (the role of fungal microbiota in acne is discussed later in this review) . Hence, many skin microbes may play dual roles in health and disease, and the differences in their function may lie at the strain or subspecies level …”
Section: Acne and Skin Bacteriamentioning
confidence: 99%
“…While generally accepted as the cause of seborrhoeic dermatitis, M. globosa has also been shown to secrete a potentially beneficial protease, which may prevent S. aureus biofilm formation (the role of fungal microbiota in acne is discussed later in this review). 42 Hence, many skin microbes may play dual roles in health and disease, and the differences in their function may lie at the strain or subspecies level. 16,[43][44][45][46] Multiple C. acnes studies have led to the classification of subspecies or types, each displaying a unique set of characteristics, activities and pathogenic potential.…”
Section: Acne and Skin Bacteriamentioning
confidence: 99%